2011
DOI: 10.1253/circj.cj-09-0940
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Volumetry of Chronic Total Occlusion Plaque Using Coronary Multidetector Computed Tomography

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp espite remarkable progress in the technique of percutaneous coronary intervention (PCI), the recanalization of chronic total occlusion (CTO) of native coronary artery remains as one of the major challenges in interventional cardiology. 1-4 The success rates of top level operators are still considerably lower than those achieved in non-occluded coronary arteries or acutely occluded arteries by average-volume operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…In our study, the calcification did not affect the procedural result, which is similar to our prior study (16). This finding is partially explained by the poor performance of CTA for discrimination of hard fibrous tissue from calcified tissue, which shows distinct HU values but blocks guidewire advancement, or for detection of small calcification (13,26).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the calcification did not affect the procedural result, which is similar to our prior study (16). This finding is partially explained by the poor performance of CTA for discrimination of hard fibrous tissue from calcified tissue, which shows distinct HU values but blocks guidewire advancement, or for detection of small calcification (13,26).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the lack of visualization of the occluded CTO segments, CCA remains the reference standard for evaluating coronary anatomy (2,14,15). Recently, the superiority of coronary computed tomography angiography (CTA) for directly observing morphological characteristics of occluded lesions, especially calcification, was highlighted (14,15).…”
mentioning
confidence: 99%
“…Recently, the superiority of coronary computed tomography angiography (CTA) for directly observing morphological characteristics of occluded lesions, especially calcification, was highlighted (14,15). Rolf et al (3) found that pre-procedural coronary CTA was associated with a higher PCI success rate than lack of preprocedural coronary CTA.…”
mentioning
confidence: 99%
“…2 Despite the complete interruption of antegrade coronary artery blood flow caused by heavy atherosclerotic plaque burden, clinical recognition of myocardial infarction (MI) can be challenging. [3][4][5][6] The latter can have important implications especially with respect to decisions regarding myocardial revascularization.…”
mentioning
confidence: 99%